Hormone Replacement Therapy And Breast Cancer- A Case Control Study - Zaman, F; Haque, M; Islam, MZ; Yasmin, R; Azim, E (Bangladesh Medical Journal, 2012)
The present study was undertaken to asses any association between hormone replacement therapy (HRT) and breast cancer. This hospital based case -control study was conducted among sixty cases of diagnosed female breast cancer patients and age matched seventy controls of women without breast cancer and any breast complaints (pain or lump in the breast, any discharge through the nipple) during the period of January to June 2009. Data was collected at National Institute of Cancer Research, Hospital (NICRH), Mohakhali, Dhaka, Ahsania Mission Cancer Hospital, Mirpur, Dhaka, and Delta Medical college Hospital Mirpur Dhaka. Controls were selected from the women who attended those hospitals for other treatment and relatives of the breast cancer patients. The findings revealed cases (30%) took hormone therapy in comparison to the controls (7.1%) and this difference was statistically significant ( 2test, p<0.01). Users of hormone replacement therapy were more than five times more likely to develop breast cancer than the non-users. Majority of the cases (56%) and only 20% of the controls took combined form of HRT. On the contrary, 44% cases and 80% control took single form of hormone replacement therapy. The study found a significant association between hormone replacement therapy and occurrence of breast cancer. Odds ratio showed that the combined HRT users were more than 5 times more likely to develop breast cancer than the single form of HRT users. The Odds ratio also revealed that the HRT users were more than five times more likely to develop breast cancer than the HRT non-users. The study recommended specific measures and interventions to reduce the burden of breast cancers caused by HRT. DOI: http://dx.doi.org/10.3329/bmj.v39i3.9947 BMJ 2010; 39(3)